2013
DOI: 10.1111/apha.12145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a mixture of bovine milk oligosaccharides, Lactobacillus rhamnosus NCC4007 and long‐chain polyunsaturated fatty acids on catch‐up growth of intra‐uterine growth‐restricted rats

Abstract: The nutritional intervention promoted catch-up growth and normalized excessive adiposity in IUGR animals at short-term. The benefits did not extend after a period of HFD. IUGR and early diet had gender-dependent effects on hepatic gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Castaneda-Gutierrez et al . administered a mixture of prebiotic bovine milk oligosaccharides, a probiotic Lactobacillus rhamnosus strain and long-chain polyunsaturated fatty acids to LB rats from 7 to 58 days of life, and significantly reduced the fat accumulation at 58 days of age 49 . Prebiotics, probiotics and long-chain polyunsaturated fatty acids can modulate the composition and/or metabolism of gut bacteria 42 50 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Castaneda-Gutierrez et al . administered a mixture of prebiotic bovine milk oligosaccharides, a probiotic Lactobacillus rhamnosus strain and long-chain polyunsaturated fatty acids to LB rats from 7 to 58 days of life, and significantly reduced the fat accumulation at 58 days of age 49 . Prebiotics, probiotics and long-chain polyunsaturated fatty acids can modulate the composition and/or metabolism of gut bacteria 42 50 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Line studies have indicated that butyrate (SCFA produced by probiotic in colon) can reduce promoter methylation in colorectal cancer cells, and Bifidobacterium breve can reduce the expression of interleukins genes in intestinal culture model with epigenetic processes, including the enhancement of DNA methylation and the inhibition of histone acetylation. A study by Castaneda-Gutierrez et al (2014) revealed that a nutritional mixture containing Lactobacillus rhamnosus increased the expression of genes related to lipid metabolism in rats, but did not have any effect on DNA methylation. In another study by Worthley et al (2009), the consumption of synbiotics supplementation was associated with the reduction in MINT2 PMR (percentage of methylated reference) within normal colorectal mucosa, but their intervention did not have any effect on other genes like CDKN2A, MINT, MINT31, MGMT, and MLH1.…”
Section: Discussionmentioning
confidence: 99%
“…The various nutritional interventions have been developed to optimize the growth and health of IUGR neonates [ 12 14 ]. Nucleotides are a group of bioactive agents playing important roles in nearly all biochemical processes, such as transferring chemical energy, biosynthetic pathways and coenzyme components [ 15 ].…”
Section: Introductionmentioning
confidence: 99%